2003
DOI: 10.1002/j.2161-0045.2003.tb00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Mentoring: Alternative Sources and Functions of Developmental Support

Abstract: Content analyses were used to explore alternative sources and functions of developmental support other than mentoring among nonfaculty university employees. The majority of participants reported that they had an alternative source of developmental support outside of a mentoring relationship, that the developmental functions (i.e., kinds of support) provided by these sources varied, and that there were differences in sources and functions by participant age and gender. The alternative source of support most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 32 publications
4
49
0
2
Order By: Relevance
“…Several studies were conducted using a direct effects model to investigate mentorship program based on different samples like perceptions of 88 participants of a large south eastern university in United States (Allen & Finkelstein, 2003), perceptions of 18 students at University of Brighton, United Kingdom (Dutton, 2003), perceptions of 110 students in Canadian colleges (Bernier et al, 2005) and perceptions of 196 students in teaching based higher learning institutions in Sarawak . These studies found that the ability of mentors to properly implement comfortable communication and provide adequate support in formal and/or informal mentorship relationships had been important determinants of mentees' psychosocial development in the respective organizations (Allen & Finkelstein, 2003;Bernier et al, 2005;Dutton, 2003;.…”
Section: Relationship Between Mentorship Program and Mentees' Psychosmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were conducted using a direct effects model to investigate mentorship program based on different samples like perceptions of 88 participants of a large south eastern university in United States (Allen & Finkelstein, 2003), perceptions of 18 students at University of Brighton, United Kingdom (Dutton, 2003), perceptions of 110 students in Canadian colleges (Bernier et al, 2005) and perceptions of 196 students in teaching based higher learning institutions in Sarawak . These studies found that the ability of mentors to properly implement comfortable communication and provide adequate support in formal and/or informal mentorship relationships had been important determinants of mentees' psychosocial development in the respective organizations (Allen & Finkelstein, 2003;Bernier et al, 2005;Dutton, 2003;.…”
Section: Relationship Between Mentorship Program and Mentees' Psychosmentioning
confidence: 99%
“…These studies found that the ability of mentors to properly implement comfortable communication and provide adequate support in formal and/or informal mentorship relationships had been important determinants of mentees' psychosocial development in the respective organizations (Allen & Finkelstein, 2003;Bernier et al, 2005;Dutton, 2003;.…”
Section: Relationship Between Mentorship Program and Mentees' Psychosmentioning
confidence: 99%
See 1 more Smart Citation
“…Their biographical interview study of significant peer relationships identifies the information peer (sharing information with the protégé), the collegial peer (providing career strategizing, job-related feedback, and friendship), and the special peer (providing confirmation, emotional support, personal feedback, and friendship). Based on the answers on two open-ended questions of a larger survey, Allen and Finkelstein (2003) found that family members, supervisors, colleagues, subordinates, and friends provide comparable developmental support as mentors do. However, for a long time, mentoring studies ignored the influence of others on the protégé's career development.…”
Section: The Context Of Mentoringmentioning
confidence: 99%
“…that which has helped you learn, grow and develop on the job (Allen & Finkelstein, 2003). McDougall and Beattie (1997) In the literature many models of coaching can be found that represent a range of staff development practices.…”
Section: Peer Mentoring and Peer Coachingmentioning
confidence: 99%